Über die Konvergenz von Summen einer zufälligen Anzahl zufälliger Stufenprozesse - Freyer, B. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Б. Фрайер. О сходимости сумм случайного числа ступенчатых процессов B. Frajeris. Apie laiptuotų procesų atsitiktinio skaičiaus sumų konvergavimą